Surgical therapy of chronic pancreatitis: clinical results and health-related quality of life - Benzing, Christian; Hau, Hans-Michael; Atanasov, Georgi; Krenzien, Felix; Eisenhauer, Tim; Broschewitz, Johannes; Bartels, Michael; Schmelzle, Moritz; Wiltberger, Georg (Zeitschrift für Gastroenterologie, 2018)
Introduction There are several well-established surgical procedures for the treatment of chronic pancreatitis (CP). The present study seeks to evaluate the perioperative and long-term outcome of these procedures.Methods All patients who had undergone pancreaticoduodenectomy (PD), duodenum-preserving pancreatic head resection (DPPHR), and distal pancreatectomy (DP) for CP were retrospectively analyzed with regards to the perioperative outcome and long-term survival. Health-related quality of life (HRQoL) was assessed using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire.Results There were 145 patients available for analysis. Major complications (grade IIIb–V) occurred in 19 %, in-hospital mortality was 4.2 %, and 90-day mortality was 3 % with no differences between the different resection groups (all p > 0.05). Ten-year survival was 58 % and was highest in the DP group (100 %) but without statistical significance (p = 0.72). The response rate of the HRQoL assessment was 45 % (65 of 145). There was a significant improvement with regards to pain and HRQoL of all resection groups compared to the preoperative group (all p < 0.05). With respect to HRQoL and pain relief, the PD, DPPHR, and DP did not differ significantly.Discussion Surgical therapy of CP can be performed safely. The 3 different types of resection performed equally with regards to complications and HRQoL.
Keywords: chronic pancreatitis; surgical therapy; pancreaticoduodenectomy; duodenum-preserving pancreatic head resection; distal pancreatectomy; quality of Life